Developing a core set of indicators for quality assessment of cancer genetic services. (30th September 2020) - Unim, B; Sindoni, A; Pitini, E; Vacchio, M R; Marzuillo, C; De Vito, C; Villari, P
Abstract: Background: One of the major challenges of personalized medicine is how to assess the quality of genetic services offered both in public and private sectors. Although the quality of genetic services can be assessed and compared with structure, process or outcome measures, a consensus on the appropriate quality assessment measures is lacking worldwide. The aim of the study is to develop a core set of indicators for the quality assessment of genetic services providing testing for breast and ovarian cancer (BRCA1/2 testing). Methods: In the first phase, a literature review was performed to identify genetic services providing BRCA1/2 genetic testing in Europe. In the second phase, structural, process and outcome measures retrieved from the literature records will be rated, with a 5-point Likert grading scale, by members of multinational genetic associations in a three-round Delphi survey. The survey will also accommodate quality assessment measures proposed by the participants. In the last phase, the feasibility of using a core set of indicators will be assessed across European countries. Results: The literature search yielded 92 relevant records published 2000-2019, in English or Italian. The records reported outcome measures (92/92) and, to a lesser extent, process (80/92) and structure measures (71/92). An ad hoc data extraction form has been developed and the evaluation of the literature records is ongoing. Highly rated measures obtained through consensus among genetics professionals will form the core set of indicators for quality assessment of genetic services providing BRCA1/2 genetic testing. Conclusions: The development of a standardized set of indicators for the assessment of genetics services is an essential step forward in defining common quality standards of the services in Europe. It will also facilitate direct comparisons across countries, highlighting examples of good practices and points of improvement for currently implemented genetic services. Key messages: A minimum set of indicators for the assessment of genetics services is required to guarantee quality standards of the services across European countries. A core set of indicators will facilitate direct comparisons across European countries, underlining good practices and points of improvement for currently implemented genetic services.